The spatial pattern of teritory on the landscape-dwelling community Juruan Laok Village East Madura - Redi Sigit Febrianto; Lisa Dwi Wulandari; Herry Santosa (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2017)
The Madurese community is known as an individual, independent and subsistent corn farming community, identified as having three main territories: residential territory, open space territory and agricultural landscape territory. The distance between clusters of distant residential causes is referred to as individual society as well as independent. The dependence of life on crops causes the distance of dwelling with the agricultural landscape so close that it is called subsistence society. Land-based economic morality, due to the persistence of maintaining spatial territory. So the fundamental question of research is how the third spatial pattern of territory in the village of Laok Madura Madura? The strategy used is ethnography, with qualitative research design. The main data collection methods were in-depth interviews, no open questions, with typical case sampling techniques in four occupancy based on five criteria: civitas, activity, shelter pattern, agricultural landscape pattern and artifacts existence of crop storage object. Internal validation in the form of observation, measurement and architectural documentation, caused by the characteristic of ethnic sub-ethnic of Madura, so that the head of village is not a source of internal validation, but the participant as the owner of the dwelling. The analysis is done by comparing with anthropological-architectural concept, human space concept, also with related theme study. The results obtained at least found the embodiment of the concept of spatial patterns called habitat. The concept of a spatial pattern called habitat consists of: place, environment and landscape. The arrangement of the three forms a hierarchical bubble that places in the environment, while place and environment are in the landscape. Referring to the concept of architectural-anthropological, the hierarchy of these three elements is referred to as: habitat.